2022
DOI: 10.3390/molecules27217335
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling and Biological Activity of Extracts from Nine Norwegian Medicinal and Aromatic Plants

Abstract: There is an increased interest in identifying beneficial compounds of plant origin that can be added to animal diets to improve animal performance and have a health-promoting effect. In the present study, nine herb species of the Norwegian wild flora or which can be cultivated in Norway were selected for phytogenic evaluation (hops, maral root, mint, oregano, purslane, rosemary, roseroot, sweet wormwood, yarrow). Dried herbs were sequentially extracted with dichloromethane (DCM), ethanol (EtOH) and finally wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
1
2
0
1
Order By: Relevance
“…Considering that numerous studies have demonstrated significant differences in the chemical composition and biological effects of Artemisia spp. based on the geographical origin of the plants, the specific plant part used for extraction, and the extraction method itself [ 11 , 29 , 30 ], our findings that chlorogenic acid is a prevalent phenolic compound in A. annua and A. vulgaris are consistent with other data from the same geographical region [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Considering that numerous studies have demonstrated significant differences in the chemical composition and biological effects of Artemisia spp. based on the geographical origin of the plants, the specific plant part used for extraction, and the extraction method itself [ 11 , 29 , 30 ], our findings that chlorogenic acid is a prevalent phenolic compound in A. annua and A. vulgaris are consistent with other data from the same geographical region [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Chlorogenic acid, isorhamnetin, kaempferol-3-O-glucoside and kaempferol-3-O-rutinoside were common in the composition of extracts from both Artemisia species. Slimestad et al [ 46 ] identified chlorogenic acid, the ester of caffeic and quinic acid, in both leaves and stalks of A. annua , while the antimicrobial potency of extracts from wormwood ( A. gmelinii ) against Gram-positive bacteria and Candida spp. was partially attributed to chlorogenic acid, which dominated the ethanolic preparation from the aerial parts of the plant [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless even recently, a number of studies reported on flavonoid composition of A . annua based on HPLC analysis on RP-18 phases only, resulting in incomplete peak assignments, mainly by missing chrysosplenetin ( 1 ) [ 6 ]; [ 7 ]; [ 8 ]; [ 9 ]. As a consequence, in the current study we aimed also at developing an LC-PDA-MS n method for providing a valuable tool for assigning compounds 1 and 2 in extracts prepared from different Artemisia species.…”
Section: Introductionmentioning
confidence: 99%